Narcotic and its Effects on Central Asia (Journal of Oriental Studies, 2022)
Drug trafficking has created many problems for the Central Asian republics and caused significant human and financial losses. The high profit and prosperity of this trade has caused terrorist and extremist religious groups in this region to move in this direction in order to consolidate their power and buy the weapons they need to use.The aim of this study was to investigate the effect of drug trafficking and the resulting organized crime in a descriptive-analytical manner and to obtain the required information from articles-books in this context, the main research question is: What effect can Narcotics have on the Central Asian countries? Findings from the research show that the use of extremist religious groups - which exist in most Central Asian countries - has posed a threat to the economic, political, security and social dimensions. Thus the Central Asian republics in order to control and management of these problems seeks to expand in the form of regional and trans-regional organizations, including the Central Asian Cooperation Organization, the Commonwealth of Independent States, the Collective Security Treaty Organization and the Shanghai Cooperation Organization, as well as the ECO to resolve tensions.